Children's language abilities at age 10 and exposure to intimate partner violence in early childhood: Results of an Australian prospective pregnancy cohort study. (January 2021) - Conway, Laura J.; Cook, Fallon; Cahir, Petrea; Brown, Stephanie; Reilly, Sheena; Gartland, Deirdre; Mensah, Fiona; Giallo, Rebecca
Abstract: Background: Approximately one in four children in Australia have mothers who experience intimate partner violence (IPV). These children are at risk of poor mental health. Less is known about their language outcomes, despite evidence that childhood adversity threatens neurodevelopment, and the home environment effects language development. Objective: This study aimed to examine the relationship between early childhood IPV exposure and language outcomes (receptive vocabulary, general language, pragmatic language) at age 10, including the influence of maternal depressive symptoms. Participants and setting: Participants were 615 mothers and their first-born child participating in a prospective, community-based pregnancy cohort study in Melbourne. Methods: Mothers reported their experience of IPV and depressive symptoms in the first and fourth year postpartum. At 10 years postpartum, children's receptive vocabulary was directly assessed and mothers reported on their child's general and pragmatic language skills. Results: Exposure to IPV was related to scores indicating poorer abilities in receptive vocabulary ( d =-0.26, p = .009), general language ( d = 0.23, p = .047) and pragmatic language skills ( d = 0.41, p < .001) at age 10. After adjusting for maternal depressive symptoms, evidence remained for the relationship with pragmatic language ( d =-0.32, p = .006), and a trend for receptive vocabulary ( d =-0.20, p = .052). Conclusions: At a community-level, children whose mothers experienced IPV during the child's first four years had poorer language skills in middle childhood than children whose mothers did not experience IPV. This is important because poor child language skills are associated with adverse outcomes across the lifespan including academic under-achievement and mental health problems. Clinical implications are discussed.